A Review of Gray Partridge Restocking in the UK and its Implications for the UK Biodiversity Action Plan - Stephen J. Browne; Francis Buner; Nicholas J. Aebischer (National Quail Symposium Proceedings, 2017)
The gray partridge Perdix perdix has been the subject of many re-introduction projects throughout the world. In earlier attempts many releases simply aimed to increase the number of individuals for harvesting. This is very different from a conservation project aiming to establish a self-sustaining population. In recent decades, the gray partridge has declined severely in abundance and it is a species of conservation concern throughout Western Europe. Until now, gray partridge releasing projects have mainly focused on releasing large numbers of captive-reared individuals, of which few survive because of heavy predation and low breeding success. We reviewed the scientific and gamekeepering literature, and found that nevertheless a number of traditional methods for rearing and releasing gray partridges exist. Although these have primarily been developed to supplement existing wild stocks to produce shootable resources, some can be re-used today for conservation purposes. The most promising system for producing birds for re-introduction and supplementation purposes is to obtain eggs from a reliable source, hatch and rear the chicks under bantams to eight weeks of age, then foster to failed pairs of wild gray partridges. A less labour-intensive alternative is to hatch and raise chicks under artificial heat and foster these to unsuccessful wild pairs. Obviously these two systems are dependent on the presence of local free-living wild birds. If no pairs of wild gray partridges are present it is necessary to establish a founder population first. We see two methods to achieve this goal, the release of coveys in autumn or of pairs in spring. An important pre-requisite to any restocking scheme is appropriate management including the provision of suitable habitat for feeding and nesting and the control of predators, otherwise restocking is unlikely to lead to long-term establishment.
Keywords: gray partridge; Perdix perdix; reintroduction; releasing; restocking